# R-0-3a-x-3a-x-x-a-dx-

Question Number 134547 by EDWIN88 last updated on 05/Mar/21
$$\mathscr{R}\:=\:\int_{\mathrm{0}} ^{\:\mathrm{3}{a}} {x}\:\sqrt{\frac{\mathrm{3}{a}−{x}}{{x}+{a}}}\:{dx}\: \\$$
Answered by liberty last updated on 05/Mar/21
$$\mathrm{by}\:\mathrm{change}\:\mathrm{of}\:\mathrm{variable}\: \\$$$$\:\mathrm{let}\:\sqrt{\frac{\mathrm{3}{a}−{x}}{{x}+{a}}}\:={h}\:\Rightarrow\:{x}=\frac{−{ah}^{\mathrm{2}} +\mathrm{3}{a}}{{h}^{\mathrm{2}} +\mathrm{1}} \\$$$$\:{dx}\:=\:−\frac{\mathrm{8}{ah}}{\left({h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\:{dh}\:{with}\:\rightarrow\begin{cases}{{x}=\mathrm{3}{a}\rightarrow{h}=\mathrm{0}}\\{{x}=\mathrm{0}\rightarrow{h}=\sqrt{\mathrm{3}}}\end{cases} \\$$$$\mathscr{R}\:=\:\int_{\sqrt{\mathrm{3}}} ^{\:\mathrm{0}} \left(\frac{\mathrm{3}{a}−{ah}^{\mathrm{2}} }{{h}^{\mathrm{2}} +\mathrm{1}}\right){h}\left(−\frac{\mathrm{8}{ah}}{\left({h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\right){dh} \\$$$$=\:\mathrm{8}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\sqrt{\mathrm{3}}} \left(\frac{{h}^{\mathrm{2}} \left(\mathrm{3}−{h}^{\mathrm{2}} \right)}{\left({h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{3}} }\right){dh}\: \\$$$$=\mathrm{8}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\sqrt{\mathrm{3}}} \left(\mathrm{3}{h}−{h}^{\mathrm{3}} \right).\left(\frac{{h}}{\left({h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{3}} }\right){dh} \\$$$$\mathrm{applying}\:\mathrm{integration}\:\mathrm{by}\:\mathrm{parts} \\$$$$\mathrm{with}\:\begin{cases}{\mathrm{u}=\mathrm{3h}−\mathrm{h}^{\mathrm{3}} \Rightarrow\mathrm{du}=\mathrm{3}−\mathrm{3h}^{\mathrm{2}} \:\mathrm{dh}}\\{\mathrm{v}=−\frac{\mathrm{1}}{\mathrm{4}\left(\mathrm{h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }}\end{cases} \\$$$$\mathscr{R}\:=\:\mathrm{8}{a}^{\mathrm{2}} \:\left[−\frac{\mathrm{3}{h}−{h}^{\mathrm{3}} }{\mathrm{4}\left({h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\right]_{\mathrm{0}} ^{\sqrt{\mathrm{3}}} +\mathrm{2}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\sqrt{\mathrm{3}}} \frac{\left(\mathrm{3}−\mathrm{3h}^{\mathrm{2}} \right)}{\left(\mathrm{h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\mathrm{dh} \\$$$$=\:\mathrm{0}\:+\:\mathrm{2}{a}^{\mathrm{2}} \:\int_{\mathrm{0}} ^{\:\sqrt{\mathrm{3}}} \left(\frac{\mathrm{3}−\mathrm{3h}^{\mathrm{2}} }{\left(\mathrm{h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\right)\mathrm{dh} \\$$$$=\:\mathrm{6}{a}^{\mathrm{2}} \:\int_{\mathrm{0}} ^{\sqrt{\mathrm{3}}} \left(\frac{\mathrm{1}−\mathrm{h}^{\mathrm{2}} }{\left(\mathrm{h}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }\right)\mathrm{dh} \\$$$$\mathrm{let}\:\mathrm{h}\:=\:\mathrm{tan}\:\varphi\:\Rightarrow\mathrm{dh}\:=\:\mathrm{sec}\:^{\mathrm{2}} \varphi\:\mathrm{d}\varphi \\$$$$\mathscr{R}\:=\:\mathrm{6}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\pi/\mathrm{3}} \left(\frac{\left.\mathrm{1}−\mathrm{tan}\:^{\mathrm{2}} \varphi\right)}{\mathrm{sec}\:^{\mathrm{4}} \varphi}\right)\mathrm{sec}\:^{\mathrm{2}} \varphi\:\mathrm{d}\varphi \\$$$$=\:\mathrm{6}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\pi/\mathrm{3}} \left(\mathrm{cos}\:^{\mathrm{2}} \varphi−\mathrm{sin}\:^{\mathrm{2}} \varphi\right)\mathrm{d}\varphi \\$$$$=\:\mathrm{6}{a}^{\mathrm{2}} \int_{\mathrm{0}} ^{\:\pi/\mathrm{3}} \left(\mathrm{cos}\:\mathrm{2}\varphi\right)\:\mathrm{d}\varphi\: \\$$$$=\:\mathrm{3}{a}^{\mathrm{2}} \:\left[\:\mathrm{sin}\:\mathrm{2}\varphi\:\right]_{\mathrm{0}} ^{\frac{\pi}{\mathrm{3}}} =\:\mathrm{3}{a}^{\mathrm{2}} ×\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}\:=\:\frac{\mathrm{3}{a}^{\mathrm{2}} \sqrt{\mathrm{3}}}{\mathrm{2}} \\$$
Answered by MJS_new last updated on 05/Mar/21
$$\int{x}\sqrt{\frac{\mathrm{3}{a}−{x}}{{x}+{a}}}{dx}= \\$$$$\:\:\:\:\:\left[{t}=\sqrt{\frac{\mathrm{3}{a}−{x}}{{x}+{a}}}\:\rightarrow\:{dx}=−\frac{\sqrt{\left(\mathrm{3}{a}−{x}\right)\left({x}+{a}\right)^{\mathrm{3}} }}{\mathrm{2}{a}}{dt}\right] \\$$$$=\mathrm{8}{a}^{\mathrm{2}} \int\frac{{t}^{\mathrm{2}} \left({t}^{\mathrm{2}} −\mathrm{3}\right)}{\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{3}} }{dt}= \\$$$$\:\:\:\:\:\left[\mathrm{Ostrogradski}\right] \\$$$$=−\frac{\mathrm{8}{a}^{\mathrm{2}} {t}^{\mathrm{3}} }{\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }+\mathrm{8}{a}^{\mathrm{2}} \int\frac{\mathrm{0}}{{t}^{\mathrm{2}} +\mathrm{1}}{dt}= \\$$$$=−\frac{\mathrm{8}{a}^{\mathrm{2}} {t}^{\mathrm{3}} }{\left({t}^{\mathrm{2}} +\mathrm{1}\right)^{\mathrm{2}} }=−\frac{\sqrt{\left(\mathrm{3}{a}−{x}\right)^{\mathrm{3}} \left({x}+{a}\right)}}{\mathrm{2}}+{C} \\$$$$\Rightarrow\:\mathrm{snswer}\:\mathrm{is}\:\frac{\mathrm{3}\sqrt{\mathrm{3}}}{\mathrm{2}}{a}^{\mathrm{2}} \\$$
Commented by liberty last updated on 05/Mar/21
$$\mathrm{Ostrogradsky}\:\mathrm{popular}\:\mathrm{method} \\$$